Designing the Teaching Model for Reading Class at Senior and Junior High School - Jufri Syahrudin (International Conference on Languages and Arts, 2012)
Reading is one of the English language skills taught to the students at junior and senior high schools in  Indonesia. Based on the current syllabus, known as Kurikulum Tingkat Satuan Pendidikan (KTSP), the teaching of reading at junior and senior high schools is based on genre or kinds of texts.  In reading class, the students are provided with competences as stated in Competence Standard (Standar Kompetensi) and Basic Competence (Kompetensi Dasar) of  the syllabus.  In this case, the product of reading class is that the students are able to comprehend some kinds of texts, such as narrative, recount, descriptive, procedure text and so forth. To gain the goal of teaching reading, a teacher should design a teaching model by selecting and using appropriate methods or technique and media and related teaching activities. The method or technique and media chosen will determine the teacher’s success and the students’ achievement in the reading class. The method and media, however, are not sufficient to achieve the teaching objectives. The more important aspect the teacher should prepare is the teaching and learning activities to help the students gaining the needed competences as demanded by Kompetensi Dasar in the syllabus. For this purpose, the writer discusses how a teacher designs Rencana Pelaksanaan Pembelajaran (RPP) or Lesson Plan by referring to syllabus and how the plan can be implemented in the classroom. For this purpose, the writer gives a model of reading activities which can be applied by the teacher and how those activities are done according to the teaching stage in reading class.